(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
OBJECTIVES & AIMS:  To determine whether the known risk factors such as comorbidities like diabetes & hypertension, or smoking increase the complications of flap transfer. Whether the type of flap transfer has any effect on flap related complications or on post-operative rehabilitation of patients.METHODOLOGY:This is a retrospective study conducted at GCS Hospital, Ahmedabad, between January 2020 to July 2021. Sample size is 63 patients with oral cavity cancer, out of which 21 underwent PMMC flap reconstruction, 21 underwent free ALT free flap reconstruction and 21 underwent Radial free flap reconstruction.CONCLUSION:Risks have not increased complications in free flap or PMMC group in our study. Various other studies have similar results however a larger patient pool may be needed to assess them. Though the flap related complications & donor site related complications are more with PMMC flap as compared to ALT & Radial free flap, statistically there is no significant difference. Also, in the functional post-op outcomes there is no statistically significant difference with PMMC flap, ALT free flap or Radial free flap.